Relações sociotécnicas na autoconstrução de infraestrutura urbana - Cecilia Reis Alves dos Santos (2015)
The current research investigates the self-construction of urban infrastructure from the sociotechnical relations that constitute it. To do so, it was conducted a mapping of the main actions and actors connected to the ongoing process of Jardim Getsêmani allotment in Belo Horizonte, Brazil. That is an area with 815 lots that find themselves in an irregular situation, both in the land aspect as well as in the urban aspect, which haven't stopped its growth and consolidation. The urban infrastructure at that place was self-constructed by the residents: streets, water and electric power distribution, and sewers. The narrative of self-construction was accompanied by the presentation of Jardim Getsêmani allotment in the municipal context; by topics related to laws about infrastructure development of allotments, and by analysis and guidelines provided by the Belo Horizonte municipality for the area. The main goal was describe what happened between the absence and the presence of infrastructure: which assemblages were necessary and which actors were brought together. Furthermore, it was taken into consideration what occurred to establish the absence situation, how people dealt with that and, after the construction, how the infrastructure continued in transformation and being the target of disputes. Besides the people, the objects were incorporated as entities able to modify the actions. Thereby, the report was not restricted to the social or material aspects of self-construction and infrastructure. To this end, the Actor-Network Theory was adopted based on Bruno Latour's work. This investigation intends to be a contribution to the researches about the process of constitution and transformation of the urban space starting from an emphasis in the relationship between multiple actors humans and non-humans.